Analisis Halal Knowldege dan Advertising Attractiveness terhadap Purchase Decision Pada Produk Kahf yang Dimediasi Halal Awareness - Adif, Riandy Mardhika (SAFE-Network, 2025)
This research is motivated by the increasing public interest in beauty products driven by lifestyle changes and a higher awareness of health and personal appearance. The purpose of this study is to examine the influence of halal knowledge and advertising attractiveness on purchase decisions mediated by halal awareness. This study uses a quantitative approach with data collection techniques using a questionnaire via Google Form and SEM-PLS tests as its analysis tool. The population in this study were male residents of Padang City. The sampling technique used was purposive sampling with the number of samples determined using the Slovin formula of 100 samples. The results of the data testing show that halal knowledge has a positive and significant effect on purchase decisions for Kahf products in the Padang city marketplace. Advertising attractiveness has a positive but insignificant effect on purchase decisions for Kahf skincare products in the Padang city marketplace. Halal awareness has a positive and significant effect on purchase decisions for Kahf skincare products in the Padang city marketplace. Halal knowledge and advertising attractiveness have a positive and significant effect on halal awareness. Halal knowledge has a positive and significant effect on purchase decisions mediated by halal awareness for Kahf skincare products in the Padang city marketplace. Advertising attractiveness also has a positive but insignificant effect on purchase decisions mediated by halal awareness in the Padang city marketplace. This has implications for Kahf companies to further increase the attractiveness of Kahf advertising to attract consumers.